Photoetching coated high-nickel ternary positive electrode material and preparation method thereof
The high-nickel ternary positive electrode material is coated with conductive photoresist by lithography, which solves the problem of unstable structure of the material during charging and discharging and high-temperature storage, and significantly improves its cycling performance and high-temperature stability.
Patent Information
- Application Number
- CN202411729095.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-21
AI Technical Summary
High-nickel or ultra-high-nickel ternary cathode materials are prone to surface transition metal ion dissolution, structural changes and side reactions during charging and discharging and high-temperature storage, resulting in poor circulation performance and high-temperature stability.
LiNixCoyMn1-x-y-wZrwO2 matrix powder was wet sprayed and coated by conductive photoresist to form a conductive polymer coating layer to improve the structural stability and conductivity of the material.
It effectively improves the surface structural stability, conductivity, thermal stability, charge and discharge efficiency, rate-based and cycling performance of high-nickel ternary cathode materials, while reducing production costs and simplifying process operations.
Smart Images

Figure CN119495735A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a photolithography-coated high-nickel ternary positive electrode material and a preparation method thereof. Background Art
[0002] With the rapid development of new energy vehicles and portable electronic devices, the performance requirements for lithium-ion batteries are constantly increasing. High-nickel or ultra-high-nickel ternary cathode materials have become a hot topic in the current research of lithium-ion battery cathode materials due to their high specific capacity and energy density. However, high-nickel or ultra-high-nickel ternary cathode materials are prone to surface transition metal ion dissolution, surface structure changes and surface side reactions during the charging and discharging process or high-temperature storage, resulting in poor cycle performance and high-temperature stability; in addition, the first discharge efficiency and conductivity of high-nickel or ultra-high-nickel ternary cathode materials also need to be continuously improved to broaden their application range, such as solid-state batteries.
[0003] The Chinese patent with publication number CN110429269B coats the high-nickel ternary positive electrode material by blending polymers of different properties. This method can alleviate the surface instability of the high-nickel ternary positive electrode material and improve the conductivity of the material to a certain extent. However, this method performs polymerization coating under acidic medium conditions, which will cause the dissolution of transition metals or lithium in the high-nickel material, thereby affecting the capacity of the material. Summary of the invention
[0004] The purpose of the present invention is to provide a photolithography-coated high-nickel ternary positive electrode material and a preparation method thereof, so as to overcome the problems existing in the prior art. The high-nickel ternary positive electrode material coated with a conductive polymer obtained by the present invention has a stable surface structure, good conductivity, good thermal stability, high charge and discharge efficiency, good rate performance and cycle performance, simple process operation, low production cost, and can be produced continuously.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a high-nickel ternary positive electrode material coated by photolithography, comprising the following steps: (1) Using conductive photoresist as a modifier to modify LiNi x Co y Mn 1-x-y-w Zr w The O2 matrix powder is coated by wet spraying to obtain a coated product; (2) Under the protection of an oxygen atmosphere, the coated product obtained in (1) is sequentially subjected to exposure reaction, water washing and developing treatment, drying, screening, and iron removal by light or heat radiation to obtain a high-nickel ternary positive electrode material coated with a conductive polymer; Furthermore, the (1) is specifically as follows: adding the conductive filler A, the polymer matrix B, and the photosensitive compound C into the solvent D and stirring and dissolving them to form a modified photoresist solution E, and spraying the photoresist solution E onto the LiNi x Co y Mn 1-x-y-w Zr w O2 matrix powder, stirred and heated to obtain a coated product; Furthermore, the conductive filler A is a nanometer-scale particle, specifically a mixture of one or two to five conductive metal particles; the polymer matrix B is a mixture of one or more of phenolic resin, acrylic resin, and SU-8 resin; the photosensitive compound C is a mixture of one or more of diazonaphthoquinone and iodonium salt; the solvent D is a mixture of one or more of propylene glycol methyl ether acetate, methyl isobutyl ketone, toluene, and xylene; Furthermore, the LiNi x Co y Mn 1-x-y-w Zr w The O2 matrix powder is a secondary particle with an average diameter of 3.0 to 18.0 μm and a specific surface area of 0.1 to 0.5 m 2 / g, where 0.80≤x<1.0, 0.03≤y≤0.1, 0.001≤w≤0.005; Furthermore, the mass ratio of the conductive filler A, the polymer matrix B, the photosensitive compound C and the solvent D in the photoresist solution E is: (0.1-10): (20-40): (1-20): (40-70); Furthermore, the LiNi x Co y Mn 1-x-y-w Zr w The mass ratio of O2 matrix powder to photoresist solution E is: 1: (0.05-0.5); Furthermore, in said (1), the stirring speed is 60 rpm, the time is 1 to 5 h, and the heating temperature is 50 to 100° C.; Furthermore, the exposure reaction time in (2) is 5 to 100 minutes, and the light or heat radiation is one of ultraviolet light, deep ultraviolet light, electron beam, and ion beam; the water washing and developing treatment is specifically: using one or a mixture of deionized water and anhydrous ethanol at 0-20°C for washing for 3 to 60 minutes and then dehydrating; the drying time is 1 to 5 hours, and the temperature is 100 to 200°C.
[0006] A photolithography-coated high-nickel ternary positive electrode material is obtained based on the above-mentioned photolithography-coated high-nickel ternary positive electrode material preparation method, the high-nickel ternary material includes LiNi x Co y Mn1-x-y-w Zr w An O2 substrate and a coating coated on the surface of the substrate, wherein the coating is a conductive polymer; Furthermore, the mass proportion of the coating in the high-nickel ternary positive electrode material is 0.1% to 2.0%.
[0007] The above technical solution has the following advantages or beneficial effects: The present invention provides a method for preparing a high-nickel ternary positive electrode material coated by photolithography, by using a conductive photoresist as a modifier to coat LiNi x Co y Mn 1-x-y-w Zr w The O2 matrix powder is wet spray coated, which makes full use of the excellent conductivity and structural stability of the conductive polymer, not only reducing the Li + The resistance to migration at the material interface can also inhibit the dissolution of metal particles on the material surface and surface side reactions; the conductive polymer coating is formed by a photopolymerization curing reaction, and has the characteristics of good high temperature resistance and high mechanical strength, which can effectively improve the mechanical strength of the surface particles of high-nickel or ultra-high-nickel ternary positive electrode materials; the structurally stable conductive photoresist coating can block the influence of the material surface environment, reduce residual alkali and its moisture content, help reduce the side reactions between high-nickel materials and electrolytes, inhibit the decomposition of electrolytes and HF corrosion, thereby improving the battery's cycle performance, high temperature performance and safety performance.
[0008] Furthermore, the modified photoresist solution E is sprayed into the base powder, and the coating process is promoted by stirring and heating, which can ensure that the photoresist forms a uniform and dense coating layer on the surface of the base powder; the addition of conductive filler A significantly improves the conductivity of the photoresist, so that the coated product further enhances its electron transmission ability while maintaining the original performance of the high-nickel ternary positive electrode material; the introduction of the photosensitive compound C makes the photoresist have excellent photosensitivity and can undergo a curing reaction under the action of light or thermal radiation.
[0009] Furthermore, the conductive filler A uses nano-scale particles, such as conductive metal particles or a mixture thereof, which can significantly improve the conductive properties of the coating layer. The nano-scale particles have a large specific surface area and high surface activity, which is conducive to forming a more compact and conductive coating layer; the polymer matrix B selects phenolic resin, acrylic resin, SU-8 resin, which has good film-forming properties, chemical stability and thermal stability, and can form a strong and durable coating layer; the photosensitive compound C uses diazonaphthoquinone and iodonium salt, which can react chemically under light or thermal radiation to form a stable cross-linked structure; the solvent D selects propylene glycol methyl ether acetate, methyl isobutyl ketone, toluene, and xylene, which has good solubility and volatility, and can fully dissolve the conductive filler, polymer matrix and photosensitive compound to form a uniform modified photoresist solution.
[0010] Furthermore, the average diameter of the matrix powder is in the range of 3.0 to 18.0 μm, which helps to ensure uniform distribution of particles in the battery and reduce the gaps between particles; the specific surface area is between 0.1 and 0.5 m² / g, which not only ensures good contact between particles, but also avoids side reactions and electrolyte decomposition problems that may be caused by excessive specific surface area; by adjusting the range of x, a ternary positive electrode material with a high nickel content can be obtained, and the ranges of y and w ensure the stability of the chemical composition of the matrix powder. Appropriate amounts of cobalt (Co) and manganese (Mn) and trace amounts of zirconium (Zr) doping help to improve the cycle stability and thermal stability of the material, while reducing the migration resistance of lithium ions.
[0011] Furthermore, by precisely controlling the mass ratio of each component, it is possible to ensure that the photoresist solution E has suitable viscosity, fluidity and curing properties, which helps to form a uniform and dense coating layer during the spraying and heating process, thereby improving the overall performance of the material.
[0012] Furthermore, by precisely controlling the mass ratio of the matrix powder to the photoresist solution, the thickness of the coating layer can be precisely regulated, which not only improves the conductivity of the material, but also helps to reduce the interface resistance and improve the charge and discharge efficiency and cycle stability of the battery.
[0013] Furthermore, by precisely controlling the stirring speed and heating temperature, the preparation process of the photolithography-coated high-nickel ternary positive electrode material can be optimized to improve production efficiency.
[0014] Furthermore, the exposure reaction time is set to 5 to 100 minutes, which can ensure that the photoresist solution undergoes a sufficient chemical reaction under light to form a stable coating structure; the light type is selectable, and flexible light selection helps to optimize the exposure effect and improve the quality and uniformity of the coating; the water washing and development treatment uses one or a mixture of deionized water or anhydrous ethanol, and washes at 0 to 20°C for 3 to 60 minutes, which can remove unreacted photoresist and impurities while maintaining the integrity and stability of the coating. Appropriate washing time and temperature conditions help to ensure the development effect and avoid adverse effects on material properties.
[0015] The present invention also provides a photolithography-coated high-nickel ternary positive electrode material, which fully utilizes the advantages of good conductivity and stable structure of the conductive polymer, so that the battery can not only reduce the Li + It not only solves the problem of migration resistance at the material interface, but also inhibits the dissolution of metal particles on the material surface and surface side reactions; at the same time, the metal particle filler in the polymer formed after the photopolymerization curing reaction can form a conductive network in the photoresist, which has significant electrochemical properties, especially at low temperatures, which is of great significance for improving the charge and discharge efficiency and rate performance of the battery; the use of high-nickel or ultra-high-nickel ternary positive electrode materials coated with conductive polymers not only significantly improves the electronic conductivity of the material, but also the unique conductive network constructs a rapid lithium ion deintercalation channel; on the other hand, the conductive polymer coating formed by the photopolymerization curing reaction has good high temperature resistance. , high mechanical strength, can effectively improve the mechanical strength of the surface particles of high-nickel or ultra-high-nickel ternary positive electrode materials, and avoid the problem of primary particle shedding in the subsequent treatment processes of high-nickel ternary materials such as water washing, development, and drying; at the same time, the conductive photoresist coating layer with stable structure blocks the environmental impact on the surface of the material, reduces the residual alkali and its moisture content, further reduces the side reaction between the high-nickel material and the electrolyte, inhibits the decomposition of the electrolyte and HF corrosion, and improves the cycle, high temperature and safety performance of the battery; the high-nickel ternary positive electrode material coated with the conductive photoresist obtained by the present invention has a complete crystal structure, good conductivity, high first discharge efficiency, good rate and cycle performance, simple process operation, and can be continuously produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a schematic diagram of a process for preparing a high-nickel ternary positive electrode material coated by a photolithography method of the present invention; Figure 2 This is a SEM image of Example 5 of the present invention after coating. DETAILED DESCRIPTION
[0017] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0018] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0019] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0020] The present invention provides a method for preparing a high-nickel ternary positive electrode material coated by a photolithography method, comprising the following steps: (1) Using conductive photoresist as a modifier to modify LiNi x Co y Mn 1-x-y-w Zr w The O2 matrix powder is coated by wet spraying to obtain a coated product; Specifically, the conductive filler A, the polymer matrix B, and the photosensitive compound C are added to the solvent D and stirred to dissolve to form a modified photoresist solution E, and the photoresist solution E is sprayed onto the LiNi x Co y Mn 1-x-y- w Zr w O2 matrix powder, stirred at 60 rpm for 1 to 5 h and heated to 50 to 100°C, preferably 60 to 80°C, to obtain a coated product; Preferably, the conductive filler A is a nanometer-scale particle, specifically one or a mixture of 2 to 5 particles of silver, gold, zirconium, tungsten, cobalt, aluminum, magnesium, titanium, lithium, sodium, niobium, bismuth, and cerium conductive metal particles; the polymer matrix B is a mixture of one or more of phenolic resin, acrylic resin, and SU-8 resin; the photosensitive compound C is a mixture of one or more of diazonaphthoquinone and iodonium salt; the solvent D is a mixture of one or more of propylene glycol methyl ether acetate, methyl isobutyl ketone, toluene, and xylene; Preferably, LiNi x Co y Mn 1-x-y-w Zr w The O2 matrix powder is a secondary particle with an average diameter of 3.0 to 18.0 μm and a specific surface area of 0.1 to 0.5 m 2 / g, where 0.80≤x<1.0, 0.03≤y≤0.1, 0.001≤w≤0.005; Preferably, the mass ratio of the conductive filler A, the polymer matrix B, the photosensitive compound C and the solvent D in the photoresist solution E is: (0.1-10): (20-40): (1-20): (40-70); (2) Under the protection of an oxygen atmosphere, the coated product obtained in (1) is sequentially exposed to light or heat radiation for 5 to 100 minutes, washed with deionized water or anhydrous ethanol at 0-20° C. for 3 to 60 minutes, dehydrated, dried at 100 to 200° C. for 1 to 5 hours, sieved, and iron removed to obtain a high-nickel ternary positive electrode material coated with a conductive polymer; Preferably, the light or thermal radiation is one of ultraviolet light, deep ultraviolet light, electron beam, and ion beam; Preferably, the exposure reaction time is 50 to 100 min, and the washing time is 10 to 30 min; The present invention also provides a photolithography-coated high-nickel ternary positive electrode material, based on the above-mentioned photolithography-coated high-nickel ternary positive electrode material preparation method, the high-nickel ternary material includes LiNi x Co y Mn 1-x-y-w Zr w An O2 matrix and a coating coated on the surface of the matrix, wherein the coating is a conductive polymer, and the mass proportion of the coating in the high-nickel ternary positive electrode material is 0.1% to 2.0%.
[0021] Embodiment 1: like Figure 1 As shown, this embodiment provides a photolithography-coated high-nickel ternary positive electrode material and a preparation method thereof, comprising the following steps: (1) Nano-aluminum particle conductive filler, phenolic resin, and naphthoquinone diazide were mixed in a mass ratio of 5:25:10, added into a propylene glycol methyl ether acetate solvent accounting for 60% by mass, and stirred to dissolve evenly to obtain a modified conductive photoresist solution containing aluminum particles. The modified conductive photoresist solution containing aluminum particles was sprayed onto a surface containing LiNi at a mass ratio of 0.05:1. 0.798 Co 0.1 Mn 0.1 Zr 0.002The O2 matrix powder was placed in a reactor and stirred at 60 rpm for 5 h and heated to 80 °C to obtain a coated product; (2) Under the protection of an oxygen atmosphere, the coated product obtained in (1) was exposed to ultraviolet light for 30 minutes, washed with deionized water at 10°C for 30 minutes, dehydrated, dried at 130°C for 3 hours, sieved, and iron removed to obtain a high-nickel ternary positive electrode material coated with an aluminum-containing conductive polymer.
[0022] This embodiment also provides a photolithography-coated high-nickel ternary positive electrode material, based on the above-mentioned photolithography-coated high-nickel ternary positive electrode material preparation method, the high-nickel ternary material includes LiNi 0.798 Co 0.1 Mn 0.1 Zr 0.002 O2 substrate and coating coated on the surface of the substrate, LiNi 0.798 Co 0.1 Mn 0.1 Zr 0.002 The average diameter of the O2 matrix is 8.0 μm and the specific surface area is 0.4 m 2 / g, the coating is a conductive polymer, and the mass proportion of the coating in the high-nickel ternary positive electrode material is 0.5%.
[0023] Embodiment 2: like Figure 1 As shown, this embodiment provides a photolithography-coated high-nickel ternary positive electrode material and a preparation method thereof, comprising the following steps: (1) Mix nano-scale silver particle conductive filler, acrylic resin, and iodonium salt in a mass ratio of 10:35:10, add to 55% by mass of toluene solvent, stir and dissolve evenly, and obtain a modified conductive photoresist solution containing silver particles. Spray the modified conductive photoresist solution containing silver particles onto a plate containing LiNi at a mass ratio of 0.1:1. 0.798 Co 0.1 Mn 0.1 Zr 0.002 The O2 matrix powder was placed in a reactor and stirred at 60 rpm for 5 h and heated to 80 °C to obtain a coated product; (2) Under the protection of an oxygen atmosphere, the coated product obtained in (1) was exposed to ultraviolet light for 50 minutes, washed with a mixture of deionized water and 30% ethanol at 10°C for 30 minutes, dehydrated, dried at 150°C for 2 hours, sieved, and iron removed to obtain a high-nickel ternary positive electrode material coated with a silver particle-containing conductive polymer.
[0024] This embodiment also provides a photolithography-coated high-nickel ternary positive electrode material, based on the above-mentioned photolithography-coated high-nickel ternary positive electrode material preparation method, the high-nickel ternary material includes LiNi 0.798 Co 0.1 Mn 0.1 Zr 0.002 O2 substrate and coating coated on the surface of the substrate, LiNi 0.798 Co 0.1 Mn 0.1 Zr 0.002 The average diameter of the O2 matrix is 10.0 μm and the specific surface area is 0.3 m 2 / g, the coating is a conductive polymer, and the mass proportion of the coating in the high-nickel ternary positive electrode material is 0.3%.
[0025] Embodiment 3: like Figure 1 As shown, this embodiment provides a photolithography-coated high-nickel ternary positive electrode material and a preparation method thereof, comprising the following steps: (1) Mix nano-scale tungsten particle conductive filler, SU-8 resin, and naphthoquinone diazide in a mass ratio of 10:35:5, add them into a xylene solvent with a mass ratio of 40%, and stir to dissolve them evenly to obtain a modified conductive photoresist solution containing tungsten particles. Spray the modified conductive photoresist solution containing tungsten particles onto a plate containing LiNi at a mass ratio of 0.2:1. 0.798 Co 0.1 Mn 0.1 Zr 0.002 The O2 matrix powder was placed in a reactor and stirred at 60 rpm for 5 h and heated to 80 °C to obtain a coated product; (2) Under the protection of an oxygen atmosphere, the coated product obtained in (1) was exposed to ultraviolet light for 40 minutes, washed with a mixture of deionized water and 30% ethanol at 10°C for 25 minutes, dehydrated, dried at 170°C for 2 hours, sieved, and iron removed to obtain a high-nickel ternary positive electrode material coated with a tungsten-containing conductive polymer.
[0026] This embodiment also provides a photolithography-coated high-nickel ternary positive electrode material, based on the above-mentioned photolithography-coated high-nickel ternary positive electrode material preparation method, the high-nickel ternary material includes LiNi 0.798 Co 0.1 Mn 0.1 Zr 0.002 O2 substrate and coating coated on the surface of the substrate, LiNi 0.798 Co 0.1 Mn 0.1 Zr 0.002 The average diameter of the O2 matrix is 12.0 μm and the specific surface area is 0.2 m2 / g, the coating is a conductive polymer, and the mass proportion of the coating in the high-nickel ternary positive electrode material is 0.2%.
[0027] Embodiment 4: like Figure 1 As shown, this embodiment provides a photolithography-coated high-nickel ternary positive electrode material and a preparation method thereof, comprising the following steps: (1) Nano-aluminum particle conductive filler, phenolic resin, and naphthoquinone diazide were mixed in a mass ratio of 5:35:10, added into a propylene glycol methyl ether acetate solvent accounting for 50% by mass, and stirred to dissolve evenly to obtain a modified conductive photoresist solution containing aluminum particles. The modified conductive photoresist solution containing aluminum particles was sprayed onto a surface containing LiNi at a mass ratio of 0.1:1. 0.897 Co 0.05 Mn 0.05 Zr 0.003 The O2 matrix powder was placed in a reactor and stirred at 60 rpm for 5 h and heated to 80 °C to obtain a coated product; (2) Under the protection of an oxygen atmosphere, the coated product obtained in (1) was exposed to ultraviolet light for 30 minutes, washed with deionized water at 10°C for 30 minutes, dehydrated, dried at 130°C for 4 hours, sieved, and iron removed to obtain a high-nickel ternary positive electrode material coated with an aluminum-containing conductive polymer.
[0028] This embodiment also provides a photolithography-coated high-nickel ternary positive electrode material, based on the above-mentioned photolithography-coated high-nickel ternary positive electrode material preparation method, the high-nickel ternary material includes LiNi 0.897 Co 0.05 Mn 0.05 Zr 0.003 O2 substrate and coating coated on the surface of the substrate, LiNi 0.897 Co 0.05 Mn 0.05 Zr 0.003 The average diameter of the O2 matrix is 9.0 μm and the specific surface area is 0.5 m 2 / g, the coating is a conductive polymer, and the mass proportion of the coating in the high-nickel ternary positive electrode material is 0.6%.
[0029] Embodiment 5: like Figure 1 As shown, this embodiment provides a photolithography-coated high-nickel ternary positive electrode material and a preparation method thereof, comprising the following steps: (1) Nano-scale silver and aluminum particle conductive fillers, acrylic resin, and iodonium salt were mixed in a mass ratio of 7:25:13, added into a toluene solvent with a mass ratio of 55%, stirred and dissolved evenly, to obtain a modified conductive photoresist solution containing silver aluminum particles, and the modified conductive photoresist solution containing silver aluminum particles was sprayed onto a surface containing LiNi at a mass ratio of 0.2:1. 0.897 Co 0.05 Mn 0.05 Zr 0.003 The O2 matrix powder was placed in a reactor and stirred at 60 rpm for 5 h and heated to 80 °C to obtain a coated product; (2) Under the protection of an oxygen atmosphere, the coated product obtained in (1) was exposed to ultraviolet light for 50 minutes, washed with a mixture of deionized water and 30% ethanol at 10°C for 20 minutes, dehydrated, dried at 150°C for 2 hours, sieved, and iron removed to obtain a high-nickel ternary positive electrode material coated with a conductive polymer containing silver aluminum particles.
[0030] This embodiment also provides a photolithography-coated high-nickel ternary positive electrode material, based on the above-mentioned photolithography-coated high-nickel ternary positive electrode material preparation method, the high-nickel ternary material includes LiNi 0.897 Co 0.05 Mn 0.05 Zr 0.003 O2 substrate and coating coated on the surface of the substrate, LiNi 0.897 Co 0.05 Mn 0.05 Zr 0.003 The average diameter of the O2 matrix is 13.0 μm and the specific surface area is 0.2 m 2 / g, the coating is a conductive polymer, and the mass proportion of the coating in the high-nickel ternary positive electrode material is 0.3%.
[0031] Embodiment 6: like Figure 1 As shown, this embodiment provides a photolithography-coated high-nickel ternary positive electrode material and a preparation method thereof, comprising the following steps: (1) Nano-scale tungsten and aluminum particle conductive fillers, SU-8 resin, and naphthoquinone diazide were mixed in a mass ratio of 10:20:5, added into a xylene solvent with a mass ratio of 60%, and stirred to dissolve evenly to obtain a modified conductive photoresist solution containing tungsten aluminum particles. The modified conductive photoresist solution containing tungsten aluminum ions was sprayed onto a substrate containing LiNi at a mass ratio of 0.2:1. 0.897 Co 0.05 Mn 0.05 Zr 0.003 The O2 matrix powder was placed in a reactor and stirred at 60 rpm for 3 h and heated to 80 °C to obtain a coated product; (2) Under the protection of an oxygen atmosphere, the coated product obtained in (1) was exposed to ultraviolet light for 60 minutes, washed with a mixture of deionized water and 30% ethanol at 10°C for 30 minutes, dehydrated, dried at 170°C for 3 hours, sieved, and iron removed to obtain a high-nickel ternary positive electrode material coated with a conductive polymer containing tungsten-aluminum particles.
[0032] This embodiment also provides a photolithography-coated high-nickel ternary positive electrode material, based on the above-mentioned photolithography-coated high-nickel ternary positive electrode material preparation method, the high-nickel ternary material includes LiNi 0.897 Co 0.05 Mn 0.05 Zr 0.003 O2 substrate and coating coated on the surface of the substrate, LiNi 0.897 Co 0.05 Mn 0.05 Zr 0.003 The average diameter of the O2 matrix is 13.0 μm and the specific surface area is 0.2 m 2 / g, the coating is a conductive polymer, and the mass proportion of the coating in the high-nickel ternary positive electrode material is 0.4%.
[0033] Embodiment 7: like Figure 1 As shown, this embodiment provides a photolithography-coated high-nickel ternary positive electrode material and a preparation method thereof, comprising the following steps: (1) Nano-aluminum particle conductive filler, phenolic resin, and naphthoquinone diazide were mixed in a mass ratio of 0.1:20:1, added into a propylene glycol methyl ether acetate solvent with a mass ratio of 40%, and stirred to dissolve evenly to obtain a modified conductive photoresist solution containing aluminum particles. The modified conductive photoresist solution containing aluminum particles was sprayed onto a surface containing LiNi at a mass ratio of 0.1:1. 0.8 Co 0.1 Mn 0.099 Zr 0.001 The O2 matrix powder was placed in a reactor and stirred at 60 rpm for 1 h and heated to 50 °C to obtain a coated product; (2) Under the protection of an oxygen atmosphere, the coated product obtained in (1) was exposed to deep ultraviolet light for 5 min, washed with deionized water at 10°C for 3 min, dehydrated, dried at 100°C for 1 h, sieved, and iron removed to obtain a high-nickel ternary positive electrode material coated with an aluminum-containing conductive polymer.
[0034] This embodiment also provides a photolithography-coated high-nickel ternary positive electrode material, based on the above-mentioned photolithography-coated high-nickel ternary positive electrode material preparation method, the high-nickel ternary material includes LiNi 0.8 Co 0.1Mn 0.099 Zr 0.001 O2 substrate and coating coated on the surface of the substrate, LiNi 0.8 Co 0.1 Mn 0.099 Zr 0.001 The average diameter of the O2 matrix is 7.0 μm and the specific surface area is 0.5 m 2 / g, the coating is a conductive polymer, and the mass proportion of the coating in the high nickel ternary positive electrode material is 1.0%.
[0035] Embodiment 8: like Figure 1 As shown, this embodiment provides a photolithography-coated high-nickel ternary positive electrode material and a preparation method thereof, comprising the following steps: (1) Mix nano-sized magnesium particle conductive filler, phenolic resin, and naphthoquinone diazide in a mass ratio of 10:40:20, add them into a propylene glycol methyl ether acetate solvent with a mass ratio of 70%, and stir to dissolve them evenly to obtain a modified conductive photoresist solution containing magnesium particles. Spray the modified conductive photoresist solution containing magnesium particles onto a substrate containing LiNi at a mass ratio of 0.5:1. 0.96 Co 0.03 Mn 0.095 Zr 0.005 The O2 matrix powder was placed in a reactor and stirred at 60 rpm for 3 h and heated to 100 °C to obtain a coated product; (2) Under the protection of an oxygen atmosphere, the coated product obtained in (1) was exposed to electron beam irradiation for 100 min, washed with deionized water at 20°C for 60 min, dehydrated, dried at 200°C for 5 h, sieved, and iron removed to obtain a high-nickel ternary positive electrode material coated with a conductive polymer containing magnesium particles.
[0036] This embodiment also provides a photolithography-coated high-nickel ternary positive electrode material, based on the above-mentioned photolithography-coated high-nickel ternary positive electrode material preparation method, the high-nickel ternary material includes LiNi 0.96 Co 0.03 Mn 0.095 Zr 0.005 O2 substrate and coating coated on the surface of the substrate, LiNi 0.96 Co 0.03 Mn 0.095 Zr 0.005 The average diameter of the O2 matrix is 15.0 μm and the specific surface area is 0.15 m 2 / g, the coating is a conductive polymer, and the mass proportion of the coating in the high-nickel ternary positive electrode material is 1.8%.
[0037] Embodiment 9: like Figure 1 As shown, this embodiment provides a photolithography-coated high-nickel ternary positive electrode material and a preparation method thereof, comprising the following steps: (1) Nano-scale cobalt particle conductive filler, phenolic resin, and naphthoquinone diazide were mixed in a mass ratio of 0.1:40:19.9, added into a propylene glycol methyl ether acetate solvent with a mass ratio of 40%, and stirred to dissolve evenly to obtain a modified conductive photoresist solution containing cobalt particles. The modified conductive photoresist solution containing cobalt particles was sprayed onto a surface containing LiNi at a mass ratio of 0.05:1. 0.897 Co 0.05 Mn 0.05 Zr 0.003 The O2 matrix powder was placed in a reactor, stirred at 60 rpm for 1 h and heated to 100 °C to obtain a coated product; (2) Under the protection of an oxygen atmosphere, the coated product obtained in (1) was exposed to ultraviolet thermal radiation for 5 min, washed with deionized water at 0 °C for 20 min, dehydrated, dried at 200 °C for 1 h, sieved, and iron removed to obtain a high-nickel ternary positive electrode material coated with a cobalt-containing particle conductive polymer.
[0038] This embodiment also provides a photolithography-coated high-nickel ternary positive electrode material, based on the above-mentioned photolithography-coated high-nickel ternary positive electrode material preparation method, the high-nickel ternary material includes LiNi 0.897 Co 0.05 Mn 0.05 Zr 0.003 O2 body and the coating coated on the surface of the substrate, LiNi 0.897 Co 0.05 Mn 0.05 Zr 0.003 The average diameter of the O2 matrix is 3.0 μm and the specific surface area is 0.5 m 2 / g, the coating is a conductive polymer, and the mass proportion of the coating in the high-nickel ternary positive electrode material is 0.1%.
[0039] Embodiment 10: like Figure 1 As shown, this embodiment provides a photolithography-coated high-nickel ternary positive electrode material and a preparation method thereof, comprising the following steps: (1) Mix nano-scale sodium particle conductive filler, acrylic resin, and iodonium salt in a mass ratio of 10:30:10, add them into a methyl isobutyl ketone solvent with a mass ratio of 50%, stir and dissolve them evenly, and obtain a modified conductive photoresist solution containing sodium particles. Spray the modified conductive photoresist solution containing sodium particles onto a substrate containing LiNi at a mass ratio of 0.5:1. 0.917 Co 0.04 Mn 0.02 Zr0.003 The O2 matrix powder was placed in a reactor and stirred at 60 rpm for 5 h and heated to 100 °C to obtain a coated product; (2) Under the protection of an oxygen atmosphere, the coated product obtained in (1) was exposed to ion beam irradiation for 100 min, washed with deionized water at 0 °C for 60 min, dehydrated, dried at 100 °C for 5 h, sieved, and iron removed to obtain a high-nickel ternary positive electrode material coated with a sodium-containing particle conductive polymer.
[0040] This embodiment also provides a photolithography-coated high-nickel ternary positive electrode material, based on the above-mentioned photolithography-coated high-nickel ternary positive electrode material preparation method, the high-nickel ternary material includes LiNi 0.917 Co 0.04 Mn 0.02 Zr 0.003 O2 substrate and coating coated on the surface of the substrate, LiNi 0.917 Co 0.04 Mn 0.02 Zr 0.003 The average diameter of the O2 matrix is 18.0 μm and the specific surface area is 0.1 m 2 / g, the coating is a conductive polymer, and the mass proportion of the coating in the high nickel ternary positive electrode material is 2.0%.
[0041] This embodiment also provides a photolithography-coated high-nickel ternary positive electrode material, based on the above-mentioned photolithography-coated high-nickel ternary positive electrode material preparation method, the high-nickel ternary material includes LiNi 0.917 Co 0.04 Mn 0.02 Zr 0.003 O2 substrate and coating coated on the surface of the substrate, LiNi 0.917 Co 0.04 Mn 0.02 Zr 0.003 The average diameter of the O2 matrix is 18.0 μm and the specific surface area is 0.1 m 2 / g, the coating is a conductive polymer, and the mass proportion of the coating in the high nickel ternary positive electrode material is 2.0%.
[0042] Comparative Example 1: The preparation of alumina dry-coated high-nickel ternary positive electrode material includes the following steps: (1) LiNi 0.798 Co 0.1 Mn 0.1 Zr 0.002 The O2 high-nickel ternary collective powder was washed with 10°C deionized water for 30 min and dried at 150°C for 2 h to obtain a washed product X; (2) adding nano-alumina and the water-washed product X into a high-speed mixer at a mass ratio of 0.2:1, and performing dry coating to obtain aluminum-coated material Y; (3) After being uniformly coated with aluminum, material Y is sintered at 500°C for 10 h in an oxygen atmosphere to obtain the target product, aluminum-coated high-nickel ternary positive electrode material.
[0043] Comparative Example 2: The preparation of high-nickel ternary positive electrode material coated with tungsten oxide by dry method includes the following steps: (1) LiNi 0.798 Co 0.1 Mn 0.1 Zr 0.002 The O2 high-nickel ternary collective powder was washed with 10°C deionized water for 30 min and dried at 150°C for 2 h to obtain a washed product X; (2) Adding nano tungsten oxide and the above-mentioned water-washed product X into a high-speed mixer at a mass ratio of 0.15:1, and performing dry coating to obtain a tungsten-coated material Y; (3) After the tungsten is uniformly coated, the material Y is sintered at 500 °C for 10 h in an oxygen atmosphere to obtain the target product, tungsten-coated high-nickel ternary positive electrode material.
[0044] Comparative Example 3: The preparation of alumina dry-coated ultra-high nickel ternary positive electrode material includes the following steps: (1) LiNi 0.897 Co 0.05 Mn 0.05 Zr 0.003 The O2 high-nickel ternary collective powder was washed with 5°C deionized water for 10 min and dried at 150°C for 2 h to obtain a washed product X; (2) adding nano-alumina, dextrin and the above-mentioned water-washed product X in a mass ratio of 0.15:1 into a high-speed mixer for dry coating to obtain aluminum-coated material Y; (3) After being uniformly coated with aluminum, the material Y is sintered at 500°C for 10 h in an oxygen atmosphere to obtain the target product, aluminum-coated ultra-high nickel ternary positive electrode material.
[0045] Comparative Example 4: The preparation of ultra-high nickel ternary positive electrode material coated with tungsten oxide and aluminum oxide by dry method includes the following steps: (1) LiNi 0.897 Co 0.05 Mn 0.05 Zr 0.003 The O2 high-nickel ternary collective powder was washed with 5°C deionized water for 10 min and dried at 170°C for 2 h to obtain a washed product X; (2) Add nano-alumina, tungsten oxide and the above-mentioned water-washed product X into a high-speed mixer at a mass ratio of 0.15:0.3:1, and perform dry coating to obtain a tungsten-aluminum coated material Y; (3) After being evenly coated with aluminum, the material Y is sintered at 500°C for 10 h in an oxygen atmosphere to obtain the target product, tungsten-aluminum-coated ultra-high nickel ternary positive electrode material.
[0046] Table 1 Comparison of the first efficiency, capacity, rate performance and 1C cycle performance of the samples prepared in Comparative Examples 1 to 4 and Examples 1 to 6
[0047] The results show that the high nickel ternary positive electrode material coated with a conductive polymer obtained by photolithography coating makes full use of the unique conductive network structure of the conductive polymer with high conductivity, so that the battery can not only reduce the Li + It not only solves the problem of migration resistance at the material interface, but also improves the electron transmission speed of the internal structure of the material, On the other hand, the conductive polymer coating formed by the photopolymerization chemical reaction has high temperature resistance and good mechanical strength, which can effectively improve the mechanical strength of the surface particles of the high-nickel ternary positive electrode material and avoid the problem of primary particle shedding in the subsequent treatment processes such as washing, developing and drying of the high-nickel ternary material. At the same time, the conductive polymer coating with stable structure can block the environmental impact on the surface of the material, reduce the residual alkali and its moisture content, further reduce the side reaction between the high-nickel material and the electrolyte, inhibit the decomposition of the electrolyte and HF corrosion, and improve the cycle and safety performance of the battery. The material has a stable surface crystal structure, good mechanical strength, conductivity, high charge and discharge efficiency, and significantly improved rate and cyclic properties compared with the control ratio. The process operation is simple, the production cost is low, and continuous production can be carried out.
[0048] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high-nickel ternary positive electrode material coated by photolithography, characterized in that: The following steps are involved: S1, using conductive photoresist as a modifier to modify LiNi x Co y Mn 1-x-y-w Zr w The O2 matrix powder is coated by wet spraying to obtain a coated product; S2, under the protection of an oxygen atmosphere, the coated product obtained in S1 is sequentially exposed to light or heat radiation, washed and developed, dried, sieved, and iron removed to obtain a high-nickel ternary positive electrode material coated with a conductive polymer.
2. The method for preparing a high-nickel ternary positive electrode material coated by photolithography according to claim 1, characterized in that: The S1 specifically comprises: adding the conductive filler A, the polymer matrix B, and the photosensitive compound C into the solvent D and stirring and dissolving them to form a modified photoresist solution E, and spraying the photoresist solution E onto the LiNi x Co y Mn 1-x-y-w Zr w O2 matrix powder, stirred and heated to obtain a coated product.
3. The method for preparing a high-nickel ternary positive electrode material coated by photolithography according to claim 2, characterized in that: The conductive filler A is a nanometer-scale particle, specifically a mixture of one or two to five conductive metal particles; the polymer matrix B is a mixture of one or more of phenolic resin, acrylic resin, and SU-8 resin; the photosensitive compound C is a mixture of one or more of diazonaphthoquinone and iodonium salt; and the solvent D is a mixture of one or more of propylene glycol methyl ether acetate, methyl isobutyl ketone, toluene, and xylene.
4. The method for preparing a high-nickel ternary positive electrode material coated by photolithography according to claim 2, characterized in that: The LiNi x Co y Mn 1-x-y-w Zr w The O2 matrix powder is a secondary particle with an average diameter of 3.0 to 18.0 μm and a specific surface area of 0.1 to 0.5 m 2 / g, where 0.80≤x<1.0, 0.03≤y≤0.1, 0.001≤w≤0.
005.
5. The method for preparing a high-nickel ternary positive electrode material coated by photolithography according to claim 2, characterized in that: The mass ratio of the conductive filler A, the polymer matrix B, the photosensitive compound C and the solvent D in the photoresist solution E is: (0.1-10) : (20-40) : (1-20) : (40-70).
6. The method for preparing a high-nickel ternary positive electrode material coated by photolithography according to claim 2, characterized in that: The LiNi x Co y Mn 1-x-y-w Zr w The mass ratio of O2 matrix powder to photoresist solution E is: 1:(0.05~0.5).
7. The method for preparing a high-nickel ternary positive electrode material coated by photolithography according to claim 2, characterized in that: The stirring speed in S1 is 60 rpm, the time is 1 to 5 h, and the heating temperature is 50 to 100 °C.
8. The method for preparing a high-nickel ternary positive electrode material coated by photolithography according to claim 1, characterized in that: The exposure reaction time in S2 is 5 to 100 minutes, and the light or thermal radiation is one of ultraviolet light, deep ultraviolet light, electron beam, and ion beam; the water washing and developing treatment is specifically: using one or a mixture of deionized water and anhydrous ethanol at 0-20°C for washing for 3 to 60 minutes and then dehydrating; the drying time is 1 to 5 hours, and the temperature is 100 to 200°C.
9. A photolithography-coated high-nickel ternary positive electrode material, obtained based on the preparation method of a photolithography-coated high-nickel ternary positive electrode material according to any one of claims 1 to 8, characterized in that: High nickel ternary materials include LiNi x Co y Mn 1-x-y- w Zr w An O2 matrix and a coating coated on the surface of the matrix, wherein the coating is a conductive polymer.
10. A photolithography-coated high-nickel ternary positive electrode material according to claim 9, characterized in that: The mass proportion of the coating in the high-nickel ternary positive electrode material is 0.1% to 2.0%.
Citation Information
Patent Citations
A high-nickel ternary cathode material coated with a blended polymer and its preparation method
CN110429269B